UHPLC-ESI-Q-TOF-MS/MS analysis, antioxidant activity combined fingerprints for quality consistency evaluation of compound liquorice tablets. Issue 49 (3rd August 2018) - Zhang, Yujing; Wang, Chao; Yang, Fangliang; Yang, Zhe; Wang, Fangren; Sun, Guoxiang
Abstract : Traditional Chinese medicines (TCM)/herbal medicines (HM) are too complicated to comprehensively investigate their quality consistency effectively with a single detection technique. Abstract : Traditional Chinese medicines (TCM)/herbal medicines (HM) are too complicated to comprehensively investigate their quality consistency effectively with a single detection technique. Hence, finding an effective, rapid, and comprehensive quality control (QC) method is of great importance for guaranteeing the safety and efficacy of TCM/HM in clinical applications. In our current research, a novel strategy of multi-wavelength fusion HPLC fingerprints and ultraviolet (UV) spectroscopic fingerprinting was proposed and successfully applied to monitor the quality consistency of compound liquorice tablets (CLT). The quality grades of 35 CLT samples from two manufacturers were successfully discriminated and evaluated by the averaged linear quantified fingerprint method (ALQFM) from a qualitative and quantitative perspective. The results showed that the UV spectroscopic fingerprints agreed well with the multi-wavelength fusion HPLC fingerprints. In addition, ultra-high-performance liquid chromatography coupled with electrospray ionization quadrupole time-of-flight mass spectrometry (UHPLC-ESI-Q-TOF-MS) was applied to investigate the chemical constituents in CLT samples, providing an important chemical structural foundation for further QC and bioactivity studies. Additionally, a simple flow injection analysis (FIA) was developed to investigate the antioxidant capacity in CLT, which was based on the scavenging of 2, 2-diphenyl-1-picrylhydrazyl radicals by antioxidants. Furthermore, the fingerprint–efficacy relationship between high-performance liquid chromatography (HPLC) fingerprints and the antioxidant activities of CLT samples was established utilizing orthogonal projection to latent structures (OPLS). In conclusion, this study indicated that integrating UHPLC-ESI-Q-TOF-MS/MS, UV spectroscopic fingerprints, and multi-wavelength fusion HPLC fingerprints coupled with the antioxidant activities reported could give important clues for further pharmacological and clinical studies of CLT. Meanwhile, it provides a practical strategy for the rapid screening and identifying of TCM/HM quality consistency.